Dwór jako zjawisko polskiej kultury w XIX i XX wieku - Tatarkiewicz, Emanuela (My University, 2013)
Rozprawa doktorska podejmuje temat wizerunku dworku szlacheckiego w literaturze polskiej – przedstawia rekonstrukcję obrazu dworu w prozie polskiej XIX i XX wieku. Dwór tworzył swoistą kulturę, której obraz zachował się w literaturze.

Doctoral thesis deals with the image of the contry estate in Polish literature, presents the depiction of the Polish country estate in the Polish prose of the 19th and 20th century. Country estates contributed largely to creating a certain culture whose image was preserved by literature.
The country estate as a phenomenon of Polish culture in the 19th and 20th century
Wydział Filologii Polskiej i Klasycznej UAM w Poznaniu
Keywords: dwór; country estate; kultura szlachecka; noble culture; ziemiaństwo; landed gentry; proza polska XIX i XX wieku; Polish prose of the 19th and 20th century; architektura dworska; manor house architecture